MiR-2188-5p promotes GCRV replication by the targeted degradation of klf2a in Ctenopharyngodon idellus. (January 2023) - Li, Yangyu; Chen, Liangming; Li, Yangyang; Deng, Ping; Yang, Cheng; Li, Yongming; Liao, Lanjie; Zhu, Zuoyan; Wang, Yaping; Huang, Rong
Abstract: Studies on host immunity evasion by aquatic viruses have largely focused on coding genes. There is accumulating evidence for the important biological functions of non-coding miRNAs in virus–host interactions. The regulatory functions of non-coding miRNAs in fish reovirus–host interactions remain unknown. Here, miR-2188-5p in grass carp ( Ctenopharyngodon idellus ), a miRNA specific to teleosts, was predicted to target the 3′ UTR of the transcription factor klf2a . A correlation analysis and dual-luciferase reporter assay revealed that miR-2188-5p could induce the degradation of klf2a . The expression of miR-2188-5p induced the degradation of klf2a in a dose-dependent manner, suppressing the type I interferon response and promoting grass carp reovirus (GCRV) replication. As determined by a co-expression analysis, klf2a inhibited viral infection when miR-2188-5p was overexpressed. The targeted degradation of klf2a by miR-2188-5p could inhibit the type I interferon response and promote the replication of GCRV; however, this targeted degradation ability was insufficient to fully inhibit GCRV infection. These results provide novel insights into the regulatory effects and biological functions of non-coding miRNAs in fish–virus interactions. Highlights: Grass carp miR-2188-5p targets the degradation of klf2a. miR-2188-5p targets klf2a, suppresses IFN1 and promotes GCRV replication. klf2a expression offsets the induced expression of the GCRV genome by miR-2188-5p.